(untitled) (World Journal of Current Medical and Pharmaceutical Research, 2020)
Background: This research contrasted the identification of Mycobacterium tuberculosis in saliva and sputum samples using Ziehl-Neelsen, Papanicolaou, and Bleach Modified Papanicolaou fluorescent microscopy. Methodology: Sputum and saliva samples were collected in a clean sterile, leak-proof, wide-mouth containers early in the morning. Each saliva and sputum sample was further divided into 3 groups, Group A: sputum stained by Ziehl-Neelsen staining method, Group B: sputum smears stained by Papanicolaou staining method, Group C: sputum smears stained by bleach modified Papanicolaou staining method. saliva and sputum infected by Papanicolaou and observed under a Fluorescent Microscope for tubercle bacilli.. Results: The results obtained from saliva stained smears showed 63.3% of cases positive in both BMP and Pap stained saliva samples and 46.6% of cases positive in ZN stained saliva samples. Further grading of the individual staining method was carried out. Scant bacilli; 20% in Pap and 10% in BMP, 1+; 30% in Pap and 33.3% in BMP, 2+;10% in Pap and 6% in BMP and 3+-3.3% in Pap and 13% in BMP. ZN stained saliva samples scant bacilli; 56.6%, 1+; 13%, 2+; 10% and 3+; nil. Sputum samples stained by BMP, Pap, and Zn showed 100% positive results (30/30). But the grading differed among individual staining techniques. Conclusion: In our study sputum samples showed 100% positivity in comparison to saliva samples with 63.33%. Though the results of the saliva sample were lower than that of the sputum samples, the BMP method used in our study is first of its kind to the best of our knowledge. It is a simpler, convenient, and economical method that can be used in routine diagnosis of TB.